Virtual Assistant for Thesis Technical Guide Using Artificial Neural Network - Mohammad Ovi Sanjaya; Saiful Bukhori; Muhammad `Ariful Furqon (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
This study focuses on finding best practice for Artificial Neural Network (ANN) implementation in the information system for student’s thesis technical instructions. The machine learning model applied sequential model, it means ANN only use 1 input layer, a hidden/dense layer and 1 output layer. The Stochastic Gradient Decent (SGD) method was applied into data training process. The results of this study are chatbot applications, and model testing using the confusion matrix. The result of model evaluation are 99,49% accuracy and 91% in F-1 score.